Response of radial growth of Pinus sylvestris var. mongolica of different stand ages to climate and extreme drought events in the semi-arid region of western Liaoning, Northeast China - Liu, Ping; Hu, Shiyu; Wei, Hongxu; He, Wenting; Zhou, Yiming; Wang, Yutao (Frontiers in Forests and Global Change, 2023)
The frequency and severity of drought events are increasing under a changing climate, trees of different stand ages respond differently to drought events, which has a great impact on the stability of forest ecosystems. In this study, we measured radial growth (RG) in cored trees from 49 forests including young stands (20–30a) and middle-aged stands (31–50a) of Pinus sylvestris var. mongolica plantations in a semi-arid area of western Liaoning, China. We evaluated the response of RG of P. sylvestris to long-term climate, and calculate three response indicators: resistance (Rt), recovery (Rc) and resilience (Rs), so as to measure the growth response of trees to drought events. Results showed that a negative correlation was detected between RG of young stands and the monthly highest temperature (MHT) in April and May. Positive correlations were found between RG of young stands and the monthly lowest temperature (MLT) across periods from September to November, when RG of young stands was also positively correlated with Palmer Drought Severity Index (PDSI) across whole-years. There was a positive correlation between RG of middle-aged stands and MLT in September, and PDSI from June to December. After the first drought event, most pine trees recovered their RG (Rc > 1, Rs > 1). However, after three consecutive drought events, Rt, Rc, and Rs of pine trees decreased significantly (p < 0.05), and Rt and Rs were less than 1. In summary, younger pine trees are more sensitive to climate change, and spring drought is more inhibitory to growth of pine trees than high summer temperatures. Pine trees have a compensation effect after experiencing drought events, but the cumulative effect of multiple drought events will gradually offset the compensation effect of trees and eventually decline in pine tree growth, while the resistance and resilience of young stands after continuous drought events were significantly lower than those of middle-aged stands, and have a higher risk of death.